Reproduction and maternal behavior in insulin-regulated aminopeptidase (IRAP) knockout mice - Pham, Vi; Burns, Peta; Albiston, Anthony L.; Yeatman, Holly R.; Ng, Leelee; Diwakarla, Shanti; Chai, Siew Yeen (Peptides (New York, N.Y. : 1980), 2009)
During human pregnancy, a circulating form of insulin-regulated aminopeptidase (IRAP EC 3.4.11.3), often termed oxytocinase or placental leucine aminopeptidase (PLAP), is present in plasma. It is proposed that circulating IRAP plays an important role in regulating the circulating levels of oxytocin and/or vasopressin during pregnancy. We assessed the reproductive and maternal profile of global IRAP knock out mice. No differences in the reproductive profile were observed, with normal gestational period, litter size and parturition recorded. However, western blot analysis of pregnant mouse serum, failed to detect IRAP, a result which was confirmed by fluorimetric IRAP enzyme assay. A review of the literature revealed that the presence of IRAP in the maternal circulation during pregnancy has been only reported in humans. Moreover, the sequence, Phe 154 Ala 155, identified as the cleavage site for the release of soluble IRAP, is restricted to members of the homindae family. Therefore the absence of IRAP from the circulation in mice, and other species during pregnancy, is due to the inability of a secretase to cleave placental IRAP to produce a soluble form of the enzyme. Given the expression of IRAP in areas of the brain associated with oxytocin modulated maternal behavior, we also investigated whether the IRAP global knockout mice had improved maternal responses. Using standard tests to assess maternal behavior, including pup retrieval, feeding and nurturing, no differences between knock out and wild type dams were observed. In conclusion, the physiological significance of circulating IRAP during human pregnancy cannot be addressed by investigations on mice.